Examining the Potential Use of a Pretrial Risk Assessment Tool in King County, Washington (2009) - John Clark (My University, 2016)
Two recent reports looking at the King County court and community corrections systems have recommended that the county examine the implementation of a pretrial risk assessment tool that would be used by the Intake Services Unit to help the court identify risk levels when making pretrial release decisions. As a result of these recommendations, in 2009, King County established a Pretrial Risk Assessment Work Group for the purpose of exploring the feasibility of implementing a pretrial risk assessment tool, to be used by the Intake Services Unit of the Community Corrections Division, Department of Adult and Juvenile Detention. On July 1, 2009, King County contracted with the Pretrial Justice Institute (PJI) to work with the Pretrial Risk Assessment Work Group to examine the potential use of a pretrial risk assessment tool by the Intake Services Unit, and to determine the steps that need to be taken to lead to a successful implementation of a tool. This report presents the findings from this project. The next section presents the views of system officials regarding the potential benefits of and concerns with the implementation of a pretrial risk assessment tool, and then seeks to address each of the concerns. Following that is a section that describes the options that were presented to the Work Group for how they should proceed. The final section presents an implementation plan for the option initially selected by the group.